Mechanisms of endocrine resistance in hormone receptor-positive breast cancer - Gao, Yuan; Yu, Yang; Zhang, Mingqing; Yu, Wenjun; Kang, Lihua (Frontiers in Oncology, 2024)
Hormone receptor-positive breast cancer may recur or metastasize years or decades after its diagnosis. Furthermore, hormone receptor expression may persist in relapsed or metastatic cancer cells. Endocrine therapy is one of the most efficacious treatments for hormone receptor-positive breast cancers. Nevertheless, a considerable proportion of patients develop resistance to endocrine therapy. Previous studies have identified numerous mechanisms underlying drug resistance, such as epigenetic abnormalities in the estrogen receptor (ER) genome, activation of ER-independent ligands, and alterations in signaling pathways including PI3K/AKT/mTOR, Notch, NF-κB, FGFR, and IRE1-XBP1. This article reviews the mechanisms of endocrine resistance in hormone receptor-positive advanced breast cancer, drawing from previous studies, and discusses the latest research advancements and prospects.